Software for Hydrogenic Atoms and Orbitals Visualization - KITTIWUTTHISAKDI, Kowit; KUESENG, Ketsiri (Walailak Journal of Science and Technology (WJST), 2011)
A program was developed in java for hydrogenic atoms and orbitals visualization. The first 18 atoms in the periodic table were approximated with a hydrogenic wave-function. This simple hydrogenic wave-function allowed quick calculation for real-time interactive visualization. Electron cloud based models were employed and displayed by a ray-tracing technique. One or more orbitals that defined an atom could be selected and displayed. A user could zoom in, zoom out, and rotate the displayed cloud in real time. The approximation method for probability integrals was summation. The intensity of color at each point on the screen directly related to the integrated probability in finding the electron across the viewer%s eye path.